For Want of the Means: A Logistical Appraisal of the Stalingrad Airlift. Issue 2 (2nd April 2016) - Bates, Aaron
ABSTRACT: This article examines the failure of the Stalingrad airlift — the German Luftwaffe's effort to supply the encircled 6th Army by air during the famous Second World War battle — from a logistical perspective. Drawing upon German reports on the operation, it argues that a critical factor in the outcome of the airlift was the Luftwaffe's failure to provide its transport units with the tools they needed to maintain an adequate count of operational aircraft — tools that included airfield facilities, supplies, manpower, and even aircraft suited to the prevailing conditions. These factors, taken together, prevented the Luftwaffe from effectively employing the full potential of its transport forces, ensuring that they were unable to deliver the quantity of supplies needed to sustain the 6th Army.